mTOR inhibition impacts the flagellin-augmented inflammatory and antimicrobial response of human airway epithelial cells to Pseudomonas aeruginosa - Christine C.A. van Linge; Katina D. Hulme; Hessel Peters-Sengers; Robert F.J. Kullberg; Menno D. de Jong; Colin A. Russell; Alex F. de Vos; Tom van der Poll (PLoS ONE, 2025)
Objective The airway epithelium provides a first line of defense against pathogens by release of antimicrobial factors and neutrophil-attracting chemokines. Pseudomonas (P.) aeruginosa, a Gram-negative bacterium that expresses flagellin as an important virulence factor, is a common cause of injurious airway inflammation. The aim of our study was to determine the contribution of flagellin to the inflammatory, antimicrobial, and metabolic responses of the airway epithelium to P. aeruginosa. Furthermore, as we previously showed that targeting mTOR limited the glycolytic and inflammatory response induced by flagellin, we assessed the effect of rapamycin on human bronchial epithelial (HBE) cells stimulated with flagellated and non-flagellated P. aeruginosa. Methods Primary pseudostratified HBE cells, cultured on an air-liquid-interface, were treated on the basolateral side with medium, vehicle or rapamycin, exposed on the apical side with flagellated or flagellin-deficient P. aeruginosa, and analyzed for their inflammatory, antimicrobial, and glycolytic responses. Results Flagellin augmented the P. aeruginosa-induced expression of antimicrobial factors and secretion of chemokines by HBE cells but did not further increase the glycolytic response. Treatment of HBE cells with rapamycin inhibited mTOR activation in general and flagellin-augmented mTOR activation in particular, but did not affect the glycolytic response. Rapamycin, however, diminished the flagellin-augmented inflammatory and antimicrobial response induced by Pseudomonas. Conclusions These results demonstrate that flagellin is a significant factor that augments the inflammatory and antimicrobial response of human airway epithelial cells upon exposure to P. aeruginosa and suggest that mTOR inhibition by rapamycin in the airway epithelium diminishes these exaggerated responses.